(3EYQGH GdbQBfs - (3GdRLGL , EHQGgje Hf GdSQj Hf Sgd, CHhESMGb,J (B311 (3g` s
(3ChdgG (B:s
(3hbhdg (B((3hLjgG ai GdOfjG hGdBNQg (B)(3ef ShQg Bd YeQGf s
(3BNQgG (B:s
(3ef EYQGH bhdg JYGdi (B((3MQeJ Ydjce GdejJg hGdOe (B)(3ef ChGFd ShQg GdeGFOg aCeG GdeJdWN HGddMe agh cGddMe Md Je GdLRA GdNGeS YTQ jJdhg bhdg (B((3heG Cgd dZjQ Gddg Hg (B) s
(3SbW GdLRA GdMGOi YTQ ef gPg GdfSNI jJVef EYQGH eG Hjf bhdg JYGdi (B: (3ajg BjGJ HjfGJ ebGe EHQGgje ef ShQI Bd YeQGf Edi bhdg JYGdi (B" (3Caef CJHY QVhGf Gddg cef HGA HSNW ef Gddg (B" (3ef ShQI Bd YeQGf CjVGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B40 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B33s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(333(3b(B) s
Keywords: (3GdfMhs